1990
DOI: 10.1177/001872089003200105
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Compatibility and Information Display: Effects of Color, Space, and Objectness on Information Integration

Abstract: We report two experiments in which different features of the display of multiple channels of information are varied in their proximity to one another. The display presents three indicators of aircraft stall danger (airspeed, flaps, and bank). On some trials the stall danger is estimated, requiring information integration. On other trials the value of individual indicators is estimated, requiring focused attention. In Experiment 1 the spatial proximity between indicators and their distinctiveness in color were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
95
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 20 publications
10
95
0
3
Order By: Relevance
“…The dual coding theory (Paivio, 1990) and the proximity compatibility principle (Wickens and Andre, 1990) from the cognitive psychology literature were adopted to investigate the effects of presentation mode and information format respectively. An experiment was conducted to examine the effects of image-text versus text-only presentation mode, and the list versus array information format on users' online shopping performance and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The dual coding theory (Paivio, 1990) and the proximity compatibility principle (Wickens and Andre, 1990) from the cognitive psychology literature were adopted to investigate the effects of presentation mode and information format respectively. An experiment was conducted to examine the effects of image-text versus text-only presentation mode, and the list versus array information format on users' online shopping performance and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, as the 'Proximity Compatibility Principle' by Wickens and Carswell asserts [87], whether or not a 3D interface suits a certain task depends on whether the task itself is integrative or not in space and time [88]. If the task requires the integration of multiple sources of information, performance will be best supported when those sources are displayed in close 'proximity' (e.g.…”
Section: Analisys and Discussionmentioning
confidence: 99%
“…Sanderson, Flach, Buttigieg, and Casey (1989) also compared the relative superiority of bar graphs and object displays. They have reported two studies in which, in contrast to the findings of Wickens and Andre (1990), they found bar graphs to be superior to object displays if the bar graph had a strong emergent feature that mapped directly onto the task. It is likely that such a "strong emergent feature" caused greater cognitive attention to be paid to the variable encoded within the feature, thereby enhancing the reader's ability to cognitively process the variable.…”
mentioning
confidence: 83%
“…However, some valuable studies have been published. Wickens and Andre (1990) have reported the results of an experiment in which they compared three indicators of aircraft stall danger either as a bar graph or as combined features in an object display. These researchers found that, relative to the bar graph, the object display disrupted focused attention but improved information integration.…”
mentioning
confidence: 99%